Prosa Geschichte, Poetik, Theorie - Gamper, Michael; Efimova, Svetlana (WeltLiteraturen / World Literatures, 2021)
"Prose" refers to a largely free mode of speaking and writing that is not tethered to any normative form, and which permits a wide range of composition styles due to the openness of its content and form. In 18 chapters, this volume makes "prose" - an important but thus far insufficiently examined category of literary studies - the subject of historical, methodological, and theoretical investigations.